Intravenous Thrombolysis in Ischemic Stroke Patients With Active Cancer - Selvik, Henriette Aurora; Naess, Halvor; Kvistad, Christopher Elnan (Frontiers in Neurology, 2018)
Abstract Introduction It has been difficult to state specific guidelines for IV-tPA use in cancer patients. Many of the randomized tPA-trials included too few patients with cancer or excluded patients with cancer entirely. In this report, we aimed to study the use of IV-tPA in patients with active cancer and acute ischemic stroke. We also investigated if the cancer patients who received IV-tPA experienced adverse events. Methods All patients with ischemic stroke admitted to the Stroke Unit at Haukeland University Hospital were prospectively registered in the NORSTROKE database and every patient’s medical record was searched for cancer diagnoses. Results Of 1646 patients admitted with ischemic stroke, 82 (5.0 %) patients had active cancer. The total number of patients treated with IV-tPA was 16.2 %. Five patients with stroke and active cancer were treated with IV-tPA (6.1 %) and none suffered adverse events. Of the patients with no history of cancer, 261 (16.7 %) were treated with IV-tPA and 3,8 % experienced tPA-related adverse events. Conclusions Few patients with active cancer receive thrombolysis for acute ischemic stroke. We report 5 cancer patients (3 known and 2 occult) treated with IV-tPA for ischemic stroke without tPA-related adverse events.